Procesuālās formas defekts un tā ietekme uz pierādījumu pieļaujamību - Upenieks, Renārs (Latvijas Universitāte, 2011)
Bakalaura darba tēma ir ''Procesuālās formas defekts un tā ietekme uz pierādījumu pieļaujamību'' kriminālprocesā. Pierādījumu pieļaujamība ir viena no obligātajām pierādījumu pazīmēm un tieši procesuālās formas defekta ietekme nosaka to, vai pierādījumi ir izmantojami pierādīšanā. Tēmas aktualitāte atspoguļojas procesa virzītāju ikdienas darbā, jo neviens kriminālprocess nav iedomājams bez pierādījumiem.Darbā tika aplūkots kā šie divi tiesību institūti ir attīstījušies kā arī dažādā izpratne par tiem, apskatīti problēmjautājumi un izteikti priekšlikumi Kriminālprocesa likuma normu grozīšanai.

The subject of thid bachelor degree paper is- ‘’Legal procedure defect and its influence to evidences permissibility.’’ This subject is current in evry day basis, because in each criminal process there is some proof of evidence and describing those also acting on the legal procedure defect in those you can already make a possibility of evidence or proof that is needed. For the evidence to be legal it has to be according to the law. The purpose of this bachelor degree research is to explore one of the main properties of the given proof, permissibility of the evidence as well as how it is afected by the legal procedure defect. This bachelor degree paper work is devided in three parts. In the first part you will find the description of the both legal terms. The second part is devoted to the absolute impremissibility of the proof and about the procedural form defects on them. And finally in the third part we can see the answers to the questions that involve the limited possibility of the evidence, the exceptions that are related to the procedure defect.
Legal procedure defect and its influence to evidences permissibility
Keywords: Juridiskā zinātne